The potential of green manure to increase soil carbon sequestration and reduce the yield-scaled carbon footprint of rice production in southern China - Song-juan GAO; Shun LI; Guo-peng ZHOU; Wei-dong CAO (Journal of Integrative Agriculture, 2023)
Green manure (GM) has been used to support rice production in southern China for thousands of years. However, the effects of GM on soil carbon sequestration (CS) and the carbon footprint (CF) at a regional scale remain unclear. Therefore, we combined the datasets from long-term multisite experiments with a meta-analysis approach to quantify the potential of GM to increase the CS and reduce the CF of paddy soils in southern China. Compared with the fallow–rice practice, the GM–rice practice increased the soil C stock at a rate of 1.62 Mg CO2-eq ha–1 yr–1 and reduced chemical N application by 40% with no loss in the rice yield. The total CF varied from 7.51 to 13.66 Mg CO2-eq ha–1 yr–1 and was dominated by CH4 emissions (60.7–81.3%). GM decreased the indirect CF by 31.4% but increased the direct CH4 emissions by 19.6%. In the low and high CH4 emission scenarios, the CH4 emission factors of GM (EFgc) were 5.58 and 21.31%, respectively. The greater soil CS offset the increase in GM-derived CF in the low CH4 scenario, but it could not offset the CF increase in the high CH4 scenario. A trade-off analysis also showed that GM can simultaneously increase the CS and reduce the total CF of the rice production system when the EFgc was less than 9.20%. The variation in EFgc was mainly regulated by the GM application rates and water management patterns. Determining the appropriate GM application rate and drainage pattern warrant further investigation to optimize the potential of the GM–rice system to increase the CS and reduce the total CF in China.